Vacuum deposition onto webs, films, and foils - Bishop, Charles A. (William Andrew/Elsevier, 2011)
Roll-to-roll vacuum deposition is the technology that applies an even coating to a flexible material that can be held on a roll and provides a much faster and cheaper method of bulk coating than deposition onto single pieces or non-flexible surfaces, such as glass. This technology has been used in industrial-scale applications for some time, including a wide range of metalized packaging (e.g. snack packets). Its potential as a high-speed, scalable process has seen an increasing range of new products emerging that employ this cost-effective technology.